Notes on estimation of ARMA model (1.1) And ARMA (0,1) - جواد, لميعه باقر; علي, لمياء محمد (Journal of Economics and Administrative Sciences, 2012)
By driven the moment estimator of ARMA (1, 1) and by using the simulation some important notice are founded, From the more notice conclusions that the relation between the sign   and moment estimator for ARMA (1, 1) model that is: when the sign is positive means the root      gives invertible model and when the sign is negative means the root      gives invertible model. An alternative method has been suggested for ARMA (0, 1) model can be suitable when